International directory of company histories. Volume 175. - Grant, Tina; Gale Group (Farmington Hills, Mich. St. James Press, a part of Gale, Cengage Learning, 2016)
Provides histories of companies that are a leading influence in a particular industry or geographic location. For students, job candidates, business executives, historians and investors.
Adeo S.A. -- Aegean Airlines S.A. -- Albert Ziegler GmbH -- Apotex Inc. -- Arvin Sango Inc. -- Baldwin & Lyons, Inc. -- Biglari Holdings Inc. -- Boddie-Noell Enterprises, Inc. -- Boxmark Leather GmbH and Company KG -- California Acrylic Industries Inc. -- Carpetright plc -- Celadon Group Inc. -- China National Building Material Company Ltd. -- China National Tobacco Corporation -- Colony Brands Inc. -- Coverall North America, Inc. -- Cramo Oyj -- Cromology -- Crowe Horwath LLP -- CTB, Inc. -- David's Bridal, Inc. -- dELiA*s Inc. -- Delsey S.A. -- easyJet plc -- Eram S.A. -- Euler Hermes S.A. -- Facebook, Inc. -- The Finish Line, Inc. -- Flyers Energy, LLC -- ForFarmers Group B.V. -- Galaxy Nutritional Foods, Inc. -- George & Lynch, Inc. -- Gordon Brothers Group, LLC -- Grandi Molini Italiani S.p.A. -- Grass Roots Group plc -- Greggs plc -- Hearthside Food Solutions LLC -- Heineken N.V. -- Henri Bendel, Inc. -- HomeServe plc -- Hurrican AMT LLC -- Ice Miller LLP -- ITT Educational Services, Inc. -- Jackson Hewitt Tax Service, Inc. -- JJ Babbitt Company Inc. -- Johnny's Pizza House Inc. -- Kanebo Cosmetics, Inc. -- Kewpie Kabushiki Kaisha -- KeyW Corporation -- Kinnarps Holding AB -- La Financiere Atalian S.A. -- Lamps Plus, Inc. -- Landis+Gyr AG -- Lane Bryant, Inc. -- LDI Limited LLC -- Le Tanneur & Cie S.A. -- Lintec Corporation -- M Moser Associates -- Mapei S.p.A. -- Marston's PLC -- Marvin & Palmer Associates, Inc. -- Mary Kay Inc. -- McAlister's Corporation -- Metal Constructions of Greece S.A. (METKA) -- Mitsubishi UFJ NICOS Co., Ltd. -- The National Bank of South Carolina -- National Baseball Hall of Fame and Museum, Inc. -- National Stock Exchange of India Ltd. -- Nautic Global Group -- Neuberger Berman LLc -- Ninkasi Brewing Company -- Nippon Soda Co. Ltd. -- OnStar, LLC -- Panini SpA -- Paulaner Brauerei GmbH & Co. KG -- Peacocks Stores Ltd. -- Penney Group, Inc. -- Pepperl+Fuchs GmbH -- Pfeifer & Langen GmbH & Co. KG -- Pinterest Inc. -- PizzaExpress Ltd. -- Roots Canda Ltd. -- Royer Corporation -- Russian Aircraft Corporation (MiG) -- -- S2 Yachts, Inc. -- Sato Restaurant Systems Company Ltd. -- Shoe Carnival Inc. -- Signature Flight Support Corporation -- Slovenske Elektrarne, A.S. -- Soup Restaurant Group Ltd. -- Stella-Jones Inc. -- Suntor Holdings Ltd. -- Take and Give Needs Company Ltd. -- Tanger Factory Outlet Centers, Inc. -- TangoME, Inc. -- Toyoda Gosei Company Ltd. -- UAB Koncernas Achemos grupe -- Viasystems Group, Inc. -- Visionworks of America, Inc. -- ZeroChaos, Inc. (APC Workforce Solutions LLC).
Includes bibliographical references and indexes.
Keywords: Big business -- History -- Directories; Business enterprises -- History -- Directories; Corporations -- History -- Directories